INTERIOR DESIGN AT COFFEE SHOP AS A FACTOR INFLUENCING CUSTOMER RETENTION AND MEDIATING ROLE OF PERCEIVED CUSTOMER SATISFACTION - Azzuhri, Misbahuddin; Tanjung, Andre Damarizal (Universitas Ciputra Surabaya, 2017)
This research aims to determine the effect of Interior Design, Perceived Customer Satisfaction and Customer Retention on objects which is Captain Coffee Malang in simultaneously and mediation. This study describes the causal relationship between the variables through hypothesis testing. This research collect data with techniques by using questionnaires and literature study. This study used 120 samples are consumers and customers of Captain Coffee Malang. Sampling using purposive sampling. Test equipment used to test the research instruments namely validity, reliability, and classical assumption. The analytical method used is the path coefficient analysis. Hypothesis testing using t test using SPSS program. These results indicate that the interior design has a significant influence on customer retention. The interior design also has a significant effect on perceived customer satisfaction. Customer retention also has significant direct effect on customer retention. Interior design significantly affects customer retention through perceived customer satisfaction.